2019
DOI: 10.1016/j.mad.2019.111145
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and physical performance among older people—The Helsinki Birth Cohort Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, the authors did find that attrition increased only in older women with high LTPA at baseline but not in men. In another study from Finland, the authors also observed shorter telomere length at follow-up and greater telomere attrition during follow-up time associated with poorer physical performance after adjusting for covariates (age at baseline, smoking status, body mass index at baseline, follow-up time, and educational attainment) in women only [9]. These findings suggest that the association between physical activity and telomere length may be sex-specific.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation

Physical performance and telomere length in older adults

Martínez-Ezquerro,
Ortiz-Ramírez,
García-delaTorre
et al. 2023
Preprint
“…Nevertheless, the authors did find that attrition increased only in older women with high LTPA at baseline but not in men. In another study from Finland, the authors also observed shorter telomere length at follow-up and greater telomere attrition during follow-up time associated with poorer physical performance after adjusting for covariates (age at baseline, smoking status, body mass index at baseline, follow-up time, and educational attainment) in women only [9]. These findings suggest that the association between physical activity and telomere length may be sex-specific.…”
Section: Discussionmentioning
confidence: 89%
“…Physical performance can be defined as the functional ability of individuals to perform certain physical activities that depend on a variety of factors that positively or negatively affect their health; therefore, it is considered an indicator of health status [9].…”
Section: Introductionmentioning
confidence: 99%

Physical performance and telomere length in older adults

Martínez-Ezquerro,
Ortiz-Ramírez,
García-delaTorre
et al. 2023
Preprint
“…However, because most somatic cells lack telomerase, the length of their telomeres shortens over time, leading to senescence once the telomeres reach a threshold length. Telomeres shorten at a rate of 20–40 bases every year, and as people get older, they accumulate a high number of senescent cells, which adds to the ageing process ( Starkweather et al, 2014 ; Åström et al, 2019 ). Extrinsic variables can influence telomere shortening rates, such as smoking and vitamin insufficiency, but a balanced lifestyle with correct nutrition, exercise, and certain pharmacological therapies can reduce telomere shortening rates.…”
Section: Effect Of Hbot On Aging and Cellular Regenerationmentioning
confidence: 99%
“…The Helsinki's Birth cohort study has shown that the telomere length appeared to be associated with ageing (10). It was further elaborated that it be used as a marker of ageing in women (10).…”
Section: Use Of Telomere Length In Clinical Practice and Caveatsmentioning
confidence: 99%
“…The Helsinki's Birth cohort study has shown that the telomere length appeared to be associated with ageing (10). It was further elaborated that it be used as a marker of ageing in women (10). Till date the available literature suggests that telomere length can provide reliable information on an individual's biological age, disease risk, and overall health status.…”
Section: Use Of Telomere Length In Clinical Practice and Caveatsmentioning
confidence: 99%